Resultados gerenciais e operacionais da transferência tecnológica e monitoramento automatizado da produção em uma indústria metalúrgica de médio porte - Kremer, Cristian Dekkers (2008)
This research had as its main objective to analyze the operational and management factors of the transference and implementation of a technological innovation in an automated monitoring of the production within a medium-sized metallurgical industry, with the purpose of verifying the viability and efficacy of this system for the improvement of the production management and of the productivity. Through the approach of scientific induction, this case study was carried out in a company of intermediate size from the metallurgic sector, located in the city of Castro, Paraná State. This research was classified, from its nature point of view, as being an applied one of descriptive objective. In general, predominantly quantitative approaches were carried out from the data and results. As data collection instruments and prepared and structured questionnaires were used through directed questions, with options of pre-determined answer by the researcher. Aiming to complement the evidence of the collected data by the use of questionnaires, there were also some activities of systematic observation. The conducted research was divided into 7 groups of analysis: management of production; decision-making; performance measurement, information systems, technology: transfer and implementation, management of changes and operation. The first four groups were directed to responsible managers only. The fifth and sixth groups of analysis were directed to the managers and operators of the system. Finally, the latest group of analysis was directed to operators only. After the analysis of the results has come to an end, it was found that from the practical use of technological innovation of automated monitoring of the production, the company obtained significant improvements in its managerial and operational results. From all evidence found by the study of this case, it was concluded that there is viability in the transfer and implementation of technological innovation of automated monitoring of the production, since the opinion of the responsible managers and operators of the system demonstrates effective for improvement of activities related to the management of production, consequently increasing their productivity.